2013
DOI: 10.2134/agronj2012.0361
|View full text |Cite
|
Sign up to set email alerts
|

Residue Management Effects on Water Use and Yield of Deficit Irrigated Cotton

Abstract: Th e declining saturated thickness of the Ogallala Aquifer beneath the southern High Plains decreases irrigation well capacity and necessitates conservation of precipitation for crop use. A 3-yr dryland crop rotation of wheat (Triticum aestivum L.) followed by cotton (Gossypium hirsutum L.) with intervening 10-mo fallow periods was adapted for use with defi cit irrigation of 2.5 and 5.0 mm d -1 capacities on a Pantex silty clay loam (fi ne, mixed, superactive, thermic Torrertic Paleustoll) managed with disk (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…minimum of to 8 weeks at Tribune and Garden City, while the minimum 4-week duration maintained WUE at Colby. The cotton lint yield WUE values at Garden City were similar to experimental values measured with disk tillage at Bushland during growing seasons accumulating average monthly GDD (Baumhardt et al, 2013) but in the lower range reported by Zwart and Bastiaanssen (2004). Although simulated lint yields generally increased with irrigation amount, the calculated WUE values at Tribune and Colby were much lower by comparison because the limited CGDD was insufficient to mature the crop boll load acquired with the greater water use.…”
Section: Effects Of Emergence Irrigation Capacity and Duration On Csupporting
confidence: 72%
“…minimum of to 8 weeks at Tribune and Garden City, while the minimum 4-week duration maintained WUE at Colby. The cotton lint yield WUE values at Garden City were similar to experimental values measured with disk tillage at Bushland during growing seasons accumulating average monthly GDD (Baumhardt et al, 2013) but in the lower range reported by Zwart and Bastiaanssen (2004). Although simulated lint yields generally increased with irrigation amount, the calculated WUE values at Tribune and Colby were much lower by comparison because the limited CGDD was insufficient to mature the crop boll load acquired with the greater water use.…”
Section: Effects Of Emergence Irrigation Capacity and Duration On Csupporting
confidence: 72%
“…The research projects in Texas were conducted at the U.S. Department of Agriculture (USDA)-Agricultural Research Service (ARS), Conservation and Production Research Laboratory in Bushland, Texas (Musick and Dusek 1980;Eck 1986;Howell et al 1995;Schneider and Howell 1998;Tolk et al 1999;Baumhardt et al 2013), the Texas A&M AgriLife Research Station near Etter, Texas (Hao et al 2015a, b), and at producer sites near Lubbock, Texas (TAWC 2015). The climate is semiarid at all three locations (Table 1).…”
Section: Texasmentioning
confidence: 99%
“…They concluded that the effectiveness of mulch could vary among years due to interactions among climate, soil texture, irrigation frequency, and mulch mass. A similar study by Baumhardt et al (2013) evaluated the effects of irrigation rate, tillage method, and their interactions on maize yield, ET c , and CWUE in a wheat-maizefallow rotation from 2006 to 2009 (Table 5). They too hypothesized that retaining surface residue via conservation tillage would increase soil water storage, and therefore, improve the efficiency of deficit irrigation practice.…”
Section: Texasmentioning
confidence: 99%
“…Any practice that increases the portion of a water supply used by the crop for transpiration should increase the yields under DI. Tillage practices that reduce soil disturbance and maintain plant residues on the surface usually reduce evaporation loss and may improve infiltration and soil water storage and reduce surface runoff (Hergert et al, 1993;van Donk et al, 2010, Baumhardt et al, 2013. Improvements of the irrigation application system that increase irrigation uniformity and efficiency or reduce evaporation and losses also reduce the irrigation supply needed to achieve a target ET and yield (Evett, 2019).…”
Section: Practices That May Improve Yields Under Deficit Irrigationmentioning
confidence: 99%